القيم في الإشهار من الكم إلى الكيف - زياد, إسماعيل; بن بوزيان, عبد الرحيم (جامعة الوادي - University of Eloued, 2022)
يرصد هذا المقال التغييرات التاريخية القيمية التي طرأت على الإشهار منذ بروزه بقوة مع الثورة الصناعية في أوروبا الغربية والولايات المتحدة الأمريكية، التي كانت تنظر في البداية إلى الإشهار كقيمة اقتصادية تجارية ، لكن مع الأزمة الاقتصادية سنة 1929 استندت قيم الإشهار على المعطيات النفسية والسوسيوثقافية للمستهلك التي كان هدفها تكوين صورة ذهنية إيجابية للمستهلك عن الشركات الكبرى هذا من جهة، ومن جهة أخرى امتلاك النسق الإشهاري المستند على الصورة قدرة على تحويل القيم النفسية والسوسيوثقافية إلى قيم اقتصادية بحكم أن نوع التبادل في الإشهار يكون مدفوعا بالفائدة الاقتصادية. Abstract: This article monitors the historical value changes that have occurred in advertising since its emergence strongly with the industrial revolution in Western Europe and the United States of America, which initially looked at advertising as a commercial economic value, but with the economic crisis in 1929, advertising values were based on psychological and sociocultural data OF the consumer that was Its goal is to create a positive mental image of the consumer about this big company on the one hand, and on the other hand, the advertising format based on the image has the ability to transform psychological and sociocultural values into economic values by virtue of the fact that the type of exchange in advertising is driven by economic interest
مقال
Keywords: قيم ; إشهار ; كم ; كيف; value; advertising; quantity; quality